1997
DOI: 10.1086/133959
|View full text |Cite
|
Sign up to set email alerts
|

Galactic Globular Cluster Metallicity Scale from the CA II Triplet II. Rankings, Comparisons, and Puzzles

Abstract: We compare our compilation of the W ′ calcium index for 71 Galactic globular clusters to the widely used Zinn and West (1984 ApJS, 55, 45) [Fe/H] scale and to Carretta and Gratton's (1997 A&AS, 121, 95) scale from high-dispersion spectra analyzed with Kurucz (1992, private communication) model atmospheres. We find our calcium ranking to be tightly correlated with each comparison set, in a non-linear and a linear fashion, respectively. By combining our calcium index information with the Zinn and West ranking,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
375
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(396 citation statements)
references
References 48 publications
21
375
0
Order By: Relevance
“…Where available, metallicities were compiled from the homogeneous data set of Rutledge et al (1997aRutledge et al ( , 1997b. They are based on the combined strengths of the λ8498, λ8542, and λ8662 Ca II triplet lines of red giant branch (RGB) stars that are probable GC members.…”
Section: The Colour and Metallicity Data Basementioning
confidence: 99%
See 1 more Smart Citation
“…Where available, metallicities were compiled from the homogeneous data set of Rutledge et al (1997aRutledge et al ( , 1997b. They are based on the combined strengths of the λ8498, λ8542, and λ8662 Ca II triplet lines of red giant branch (RGB) stars that are probable GC members.…”
Section: The Colour and Metallicity Data Basementioning
confidence: 99%
“…They are based on the combined strengths of the λ8498, λ8542, and λ8662 Ca II triplet lines of red giant branch (RGB) stars that are probable GC members. Rutledge et al (1997aRutledge et al ( , 1997b followed the techniques of Armandroff & Da Costa (1991) for measuring the equivalent widths of these lines, correcting them to a reference point on the RGB equal to the V magnitude of the horizontal branch, and correlating them against various [Fe/H] measurements. The metallicities given in column 5 of Table 2 of Rutledge et al (1997b) were adopted in this study, this column containing their "most probable" [Fe/H] value on the scale of Zinn & West (1984;ZW84).…”
Section: The Colour and Metallicity Data Basementioning
confidence: 99%
“…This procedure (cutting at 3 σ), after additional rejection of stars with too low a S/N to measure equivalent widths, left 437 radial velocity members to be analysed. Finally, metallicities were derived from the reduced equivalent width W (Rutledge et al 1997, Cole et al 2004 of the CaT, which we calibrated against a common reference dataset of galactic globular clusters, obtained during the same observational runs.…”
Section: Stellar Populations In Carinamentioning
confidence: 99%
“…After rejection of foreground stars and stars with too low a S/N, 487 radial velocity members were analysed. Finally, metallicities were derived from the reduced equivalent width W ′ ([1], [5]). …”
Section: Observations Reduction and Calibrationmentioning
confidence: 99%
“…Analyses of the faint Carina dSph have revealed that it contains a variety of stellar populations (e.g., [4]), exhibiting prominent old (>11 Gyr) and intermediateage (5)(6) populations. This implies that Carina must have undergone several star forming (SF) episodes with at least three significant pulses.…”
Section: Introductionmentioning
confidence: 99%